(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Kindergarten Grdelin in the city of Buzet, Istria, Croatia, was chosen to undergo a deep retrofit of the current thermotechnical system, as a part of the HORIZON 2020 HAPPEN project1. The existing shallow spiral heat exchanger field is insufficient to cover heating loads of the building. Therefore, additional BHEs were drilled and completed to determine optimal borehole heat exchanger type within the same geological environment. Four BHEs, either single U (1U) or double U (2U), with different geometrical setting and depth were tested: BHE-1 (50 m, 2U DN32 ribbed), BHE-2 (75 m, 2U DN40 ribbed), BHE-3 (100 m, 2U DN32 smooth) and BHE-4 (150 m, 1U DN45 ribbed). A thermal response test (TRT) was performed to obtain the ground thermal properties. Furthermore, synthetic TRT curves were calculated to describe temperature response in the case of different heat pulses. This was done to determine heat extraction rates and the capacity of each BHE type, according to EN14511 norm. It was established that the BHE-4 is the optimal design for heating and cooling purposes on the selected site due to positive impact of the geothermal gradient, higher initial borehole temperature and a positive effect of the ribbed inner wall. [1] This paper reflects only the view of the authors and the Commission is not responsible for any use that may be made of the information it contains.